Anatomical features decide the atypical seizure manifestation of parahypothalamic hamartomas - Liu, Chang; Hu, Wenhan; Zhang, Chao; Zheng, Zhong; Yang, Xiaoli; Wang, Xiu; Mo, Jiajie; Guo, Zhihao; Shao, Xiaoqiu; Zhang, Kai (Frontiers in Neurology, 2022)
Background: An agreement exists that the intrahypothalamic phenotype of hypothalamic hamartomas (HH) is associated with epilepsy and the parahypothalamic phenotype usually causes central precocious puberty but not neurologic comorbidities or seizures. So far, no research has confirmed the pathologic role of parahypothalamic hamartomas in epilepsy genesis and the related mechanism. Objective: To confirm whether parahypothalamic hamartomas are intrinsically epileptogenic and investigate its pathway of epilepsy genesis. Methods: We reviewed ninety-two HH-related epilepsy patients, categorized them by the classification system of Delalande and Fohlen, and further classified Type Ⅰ (corresponding to parahypothalamic HH) into three groups based on the relationship between the lesion and mammillary bodies (MB): entirely invaded (Group 1), partially connected (Group 2), and not connected at all (Group 3). We evaluated different anatomical features with the relationship to clinical manifestations. Stereo-electroencephalography (SEEG) was implanted in both HH and extra-HH cortices in different groups to confirm the epileptogenic zone. Cortico-cortical evoked potentials were also used to find out the pathologic correlation between different regions to explore the related epileptogenic network. Results: Thirteen patients were parahypothalamic HH and ten of them (76.9%) presented with non-GS only, with late-onset age and normal cognitive development, which is different from classical clinical features. SEEG proved that HH is intrinsically epileptogenic in MB-involved parahypothalamic groups, with no statistical differences in onset age (p=0.213), and lesions horizontally oriented from tuber cinereum without connection to MB were not involved in seizure genesis. The results of CCEP showed a pathologic connection between HH, middle cingulate cortex, and insular cortex. Conclusion: The parahypothalamic HH can also cause epilepsy and is very different from classic HH-related seizures, by non-GS only with late-onset age and normal cognitive development. MB is proved to be related to non-GS by the mamillo-cingulate-cortex pathway.